Single arm robotic garment folding path generation. (17th December 2017) - Petrík, Vladimír; Smutný, Vladimír; Krsek, Pavel; Hlaváč, Václav
Abstract: We address the accurate single arm robotic garment folding. The folding capability is influenced mostly by the folding path which is performed by the robotic arm. This paper presents a new method for the folding path generation based on the static equilibrium of forces. The existing approach based on a similar principle confirmed to be accurate for one-dimensional strips only. We generalize the method to two-dimensional shapes by modeling the garment as an elastic shell. The path generated by our method prevents the garment from slipping while folding on a low friction surface. We demonstrate the accuracy of this approach by comparing our paths (a) with the existing method when one-dimensional strips of different materials were modeled, and (b) experimentally with real robotic folding. Graphical Abstract: The paper proposes a robotic garment folding path generation procedure. It uses the garment model represented by a thin shell. The path computation seeks states satisfying a static equilibrium condition.